Pemberdayaan Petani Lokal Melalui Inovasi Body Scrub Berbahan Jambu Biji dan Beras Merah di Desa Marga - Ni Made Elsa Sugiantari; Leni Rosyani; Ni Kadek Ayu Mirayani; I Gusti Ayu Eka Suwintari; Ni Made Ayu Natih Widhiarini (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The increasing intensity of ultraviolet (UV) radiation due to global warming poses serious risks to skin health and has led to a rising market demand for natural-based skincare products. Jabiras Body Scrub is an innovative body care product formulated from guava and brown rice to protect and nourish the skin from UV exposure. This program aims to produce an organic-based skincare product while empowering local farmers as raw material suppliers. The target market includes men and women aged 17 and above across Indonesia, including visiting tourists. Laboratory tests show that each 50-gram package of Jabiras contains 3% vitamin C and 1% antioxidants, which are effective in improving skin condition within two weeks. The product is registered with a Business Identification Number (NIB) and has obtained Intellectual Property Rights (IPR) for its brand and promotional flyer. Marketing strategies are carried out digitally via social media and e-commerce, as well as conventionally through entrepreneurship expos and word of mouth. This initiative has reached its break-even point, with a total of 250 units sold from May to September, generating IDR 9,750,000 in revenue. This activity not only achieved its sales targets but also strengthened the foundation for a sustainable business model that supports local farmers.